교양영어 수업에서 영어자동번역기 사용에 대한 대학생의 인식 및 태도연구 ― 영작문 수업을 중심으로 - 임희주 (교양교육연구, 11(6), 2017)
본 연구는 교양영어수업을 수강하는 학습자들의 영어자동번역기 사용에 대한 전반적인 인식 및 태도를 알아보는데 목적이 있다. 본 연구의 자료 수집을 위해 연구자는 대학교 1학년에 재학 중인 166명에게 설문조사를 실시했고 영어쓰기 결과물과 학습저널지를 수집했다. 또한 연구에 참여한 5명의 학생과 인터뷰를 실시했다. 본 연구의 결과는 다음과 같다. 첫째, 학습자들은 전반적으로 자동번역기 사용에 긍정적인 태도를 보였으나 여전히 영어의 어려움이나 낮은 흥미를 보였다. 둘째로 학습자들은 번역기를 사용을 통해 어휘나 표현을 향상할 수 있을 것이라는 기대를 가지고 있었다. 하지만 영문법이나 오류에 관한 기대는 다소 부정적으로 나타났다. 마지막으로 학습자들이 실시한 영작문 과업에서 학습자들은 혼동되었던 단어/어휘를 수정하거나 문장/구를 추가하는데 번역기를 사용하였다. 따라서 본 연구의 제언은 다음과 같다. 외국어교육에서 번역기의 효과적인 사용을 위해서 학습자들에게 번역기 사용에 대한 적절한 가이드라인과 훈련이 제공되어야할 것이다. 또한 교사는 영어능력 수준에 맞는 번역기 사용에 대해 고려가 필요하며 그중 초급자에 대한 고려가 우선되어야 할 것이다. The purpose of this study is to examine the general perceptions or attitudes about using the English automatic translation by the university students in a general English class. For data collection, the researcher surveyed 166 students who are in the 1st year of university and collected their products of English writing tasks and learning journals and also interviewed 5 students who participated in the study. According to the results, the findings are as followed. Firstly, learners showed positive perception towards the use of automatic translation, but they still showed difficulty and less interest in English. Secondly, the learners expected to improve their vocabulary and expressions about English writing by utilizing the automatic translations. However, they showed little negative results in English grammar and errors. Lastly, in the learners’ English writing tasks, the learners used the automatic translations to try to modify some words/expressions or to add confusing sentences/phrases. Thus, some suggestions are provided from the study. For the effective use of the translator in the foreign language education, the learner should be provided with the guidelines and training of the translator use. Also, the teacher needs to consider the use of a translator that meets the level of English proficiency, among which consideration should be given to beginners. KCI Citation Count: 10